Development of Learning Media Uno Dare Card on Human Digestive System Material to Improve Students Learning Motivation - Khairun Nida; Sauqina Sauqina; Ellyna Hafizah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Motivation plays a crucial role in the integrated science learning process. Low learning motivation is often not due to limited ability but rather to a lack of encouragement. In integrated science learning, the human digestive system presents complex material that is difficult to visualize, resulting in decreased student learning motivation. This research aims to develop the Uno Dare Card learning media, which is feasible (valid, practical, and effective), to enhance students' learning motivation in the human digestive system material. The research method employed the ADDIE development model with 29 eighth-grade students from class VIII I of SMP Negeri 1 Martapura Kota as research subjects. The instruments used to collect data included test and non-test instruments. The research results show that the Uno Dare Card learning media is highly valid across content, presentation, language, and media feasibility, with an overall score of 0.943 in the highly valid category. The Uno Dare Card is also highly practical, and the Uno Dare Card learning media has been proven effective in enhancing learning motivation, with N-gain values in the high category. The Uno Dare Card learning media is valid, practical, and effective for teaching material on the human digestive system and for enhancing students' motivation to learn.